Pharmacokinetics of Amoxicillin: Dose Dependence After Intravenous, Oral, and Intramuscular Administration - Spyker, Daniel A. (1977)
Amoxicillin was studied in normal subjects after intravenous, oral, and intramuscular administration of 250-, 500-, and 1,000-mg doses. Serum drug levels were analyzed using a two-compartment open model, as well as area under the curve (AUC) and urinary recovery. The variations of these pharmacokinetic parameters were then examined using the three-way analysis of variance and linear regression equations. These results confirmed nearly complete oral absorption: AUC was 93% of intravenous absorption, and urinary recovery was 86%. The intramuscular administration of amoxicillin results in complete and reliable absorption with peak drug levels, AUCs, and urinary recovery equivalent to oral dosage. The absorption of lyophilized amoxicillin after intramuscular injection resulted in an AUC that was 92% of intravenous absorption and urinary recovery of 91%. The peak serum levels, time to peak, and other pharmacokinetic parameters for intramuscular injection were nearly identical to those for oral administration. Kinetics of both intramuscular and oral administration exhibited dose-dependent absorption (absorption rate constant, 1.3/h for 250 mg and 0.7/h for 1,000 mg). This resulted in relatively later and lower peak serum levels for increasing dose. Total absorption, however, showed no dose dependence, as indicated by urinary recovery and AUC, which changed by less than 10%.